Urological Care and COVID-19: Looking Forward - Prayer-Galetti, Tommaso; Motterle, Giovanni; Morlacco, Alessandro; Celso, Francesco; Boemo, Deris; Iafrate, Massimo; Zattoni, Filiberto (Frontiers in Oncology, 2020)
The recent COVID-19 pandemic represents a worldwide emergency and it is affecting healthcare at every level, including also urological care and especially oncologic patients. Recent epidemiological models show that, without effective treatment or vaccine, there will be a long-lasting phase of cohabitation with the virus. Current experts' opinions recommend performing only non-deferrable uro-oncological surgery and postponing other activities until the end of the emergency, with particular concerns regarding the safety laparoscopy. Veneto Region and Padua Province represent one of the first site of the pandemic spread of the virus outside China, thus we present our experience as a Urological Referral Center in applying a segregated-team work model of organization during the month of March 2020, with a stratified organization of activities, adequate screening and protection for patients and staff were adopted. Compared to the same period of last year even if a 19.5% reduction was experienced in overall surgical activity while maintaining a comparable proportion of oncologic robotic and laparoscopic surgery and guaranteeing care also for high priority non-oncological patients. No cases of COVID-19 infection were reported in staff members nor in patients and the number of surgical complications was comparable to that of last year. Therefore, in our opinion the recommended significant reduction in urological care, including surgical activities, is likely unrealistic in the long period with unknown effects affecting mostly oncological patients. Our experience introducing a segregated-team work model might represent a model for future planning.